Analisis Altman Z-Score Dalam Memprediksi Financial Distress Dan Dampaknya Terhadap Nilai Perusahaan Pada Sektor Consumer Non-Cyclicals Di Bursa Efek Indonesia Tahun 2022–2024 - Devica Aqilah; Pujiono Pujiono (MEASUREMENT : Jurnal Program Studi Akuntansi, 2026)
This study examines the application of the Altman Z-Score model in predicting financial distress and its subsequent effect on firm value within the consumer non-cyclicals sector of the Indonesia Stock Exchange (IDX) over the period 2022-2024. Employing a quantitative-causal research design, the study utilises secondary data drawn from the annual financial reports of listed companies selected through purposive sampling, yielding 169 firm-year observations after outlier removal. Firm value is proxied by Tobin's Q, while the Altman Z-Score serves as the principal independent variable, supplemented by liquidity (Current Ratio), operating cash flow (natural logarithm), and leverage (Debt-to-Equity Ratio) as control variables. Classical assumption tests including normality (Kolmogorov-Smirnov), multicollinearity (VIF), heteroscedasticity (Glejser), and autocorrelation (Durbin-Watson) confirm that model assumptions are satisfied following a square-root transformation of the dependent variable. Multiple linear regression results reveal that the Altman Z-Score exerts a significant positive effect on firm value (β = 0.043; p < 0.001), supporting the hypothesis that higher financial health, as captured by a higher Z-Score, translates into greater investor confidence and an elevated Tobin's Q. Liquidity and DER are also found to be statistically significant, while operating cash flow is not. The model explains approximately 54.9% of the variation in firm value (Adjusted R² = 0.549). These findings validate the applicability of the Altman Z-Score as an early-warning instrument and confirm the relevance of signalling theory in explaining market responses to corporate financial conditions in an emerging economy context.